PENYELESAIAN SENGKETA MELALUI PERADILAN ADAT ACEH - Mulyadi Nurdin (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2018)
Juridically, the implementation of customary justice has been supported by a number of laws and regulations. In various laws and regulations, it was stated explicitly that strengthening customary law and customary justice must start from the Gampong and Mukim. Dispute resolution in the adat court does not mention customary justice but directly mentions the name of government institutions such as gampong and mukim. So that customary justice is carried out traditionally in Gampong and customary settlement in Mukim. While the Mukim Adat Assembly functions as a body that maintains and develops adat, organizes customary peace, resolves and gives customary decisions on disputes and customary violations, gives legal force to things and other evidences according to adat. Procession Gampong disputes / disputes are held in the Meunasah while the Mukim adat court is held in mosques, or other places designated by the Keuchik and Imeum Mukim. Related to the procedures and conditions for resolving disputes / disputes, carried out in accordance with local customary provisions.